METHODOLOGY FOR TEACHING STUDENTS TECHNIQUES IN THE CRAWL SWIMMING - Krasnova G. M. (Galaxy International Interdisciplinary Research Journal, 2023)
The Article discusses the features of educational process in the institutions of higher physical education in the professionally oriented academic discipline “Swimming” to train highly qualified specialists for pedagogical and sports-pedagogical activities. A decrease in the level of initial swimming readiness of applicants, absence of an entrance test, and short training periods negatively affect the development of sports swimming methods, and in particular the front crawl. In this regard, it is necessary to search for an innovative organization of classes and choose an effective teaching methodology. To form a motor system, the student’s previous motor experience should be taken into account and used.